Surface-state-mediated electron transfer at nanostructured ZnO multipod/electrolyte interfaces - Parthasarathy, Meera; Ramgir, Niranjan S.; Sathe, Bhaskar R.; Mulla, Imtiaz S.; Pillai, Vijayamohanan K. (Journal of Physical Chemistry C, 2007)
Redox kinetics of cyanoferrate(III) species adsorbed at an n-type ZnO multipod/electrolyte interface is explored using electrochemical techniques like cyclic voltammetry and impedance spectroscopy. The electrochemical impedance results are analyzed using a fluctuating energy level model, assuming isoenergetic tunneling of majority carriers through the Helmholtz layer. A shift in the slope of Mott-Schottky plots (C-sc(-2) versus E) together with evidence from cyclic voltammetry shows that the electron-transfer process is mediated by surface states formed because of the adsorption of ferricyanide ions (as evident from the results of Fourier transform infrared spectroscopy). More significantly, the pH of zero charge (point of zero zeta potential, pzzp) of ZnO multipods is found to be 4.5 (from capacitance vs pH plots) compared to that of bulk ZnO (pH 9.5), which could be explained on the basis of a lowering in the work function of the nanostructured semiconductor and its consequent susceptibility to the formation of surface states. This is in excellent agreement with our earlier observation of ultralow threshold field emission with this material in the light of the linear dependence of pzzp with work function of the electrode material. The flat-band potential of the nanostructures is found to be 200 mV more negative than that reported for bulk n-type ZnO electrodes, indicating a higher doping density in the former. A three-dimensional mapping of charge distribution in the surface states is attempted by correlating the capacitance response of the system subjected to a sinusoidal potential modulation to the semiconductor electrode with that resulting from a systematic variation of the redox potential of the dissolved acceptor (achieved by varying the pH of the electrolyte) which further reveals the polyenergetic nature of the surface states.